PROSEDUR PENGEMBANGAN BAHAN AJAR - Irfan Ahmad Zain; Hilma Fathimatul Zahro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teaching materials can be interpreted as components that are closely related to the content of each subject and must be relevant to the learning objectives, characteristics of students, and strategies used in learning. However, in reality, sometimes teaching materials are used continuously without evaluation and development. However, developing teaching materials is very important because it can improve the quality of learning. The purpose of this research is to find out what and how the procedures for teaching materials are as a guide for conducting learning. This research uses a qualitative approach and descriptive analysis methods. The type of data in this research is qualitative data using content analysis. The research results found that there are four main steps that need to be taken in the procedure for developing teaching materials. Namely analysis, planning, development and evaluation.